A novel HMBS gene mutation in acute intermittent porphyria: a case report of abdominal pain, seizures, and reversible neuroimaging findings - Dong, Wentao; Zeng, Bingliang; Wang, Xiaolian; Zhang, Rui; Huang, Pei; Fan, Bing; Yuan, Min; Li, Zicong (Frontiers in Genetics, 2025)
BackgroundAcute intermittent porphyria (AIP) is a rare metabolic disorder resulting from defects in the heme biosynthesis pathway, often presenting with non-specific symptoms such as abdominal pain, seizures, and neuropsychiatric disturbances. Diagnosis is challenging due to the overlap of symptoms with other conditions, and early recognition is critical for effective treatment.Case PresentationA 24-year-old female presented with a 6-day history of persistent lower abdominal pain and generalized tonic-clonic seizures, following the consumption of seafood. Neuroimaging revealed white matter hyperintensities, and urine analysis showed dark red discoloration, suggestive of porphyria. Genetic testing confirmed a novel c.499-1_514del mutation in the HMBS gene, diagnosing AIP. The patient was treated with intravenous glucose, heme arginate, and anticonvulsants. Symptom resolution was noted within days, and follow-up MRI showed significant improvement.ConclusionThis case underscores the importance of early diagnosis and management in AIP. Genetic testing plays a crucial role in confirming the diagnosis, especially in atypical cases. Timely intervention with glucose and heme arginate, combined with supportive care, led to rapid symptom resolution, reinforcing the reversibility of AIP-associated neuroimaging changes. Clinicians should maintain a high index of suspicion for AIP in patients with unexplained abdominal and neurological symptoms to prevent long-term complications.